2022
DOI: 10.1177/08987564221089403
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Odontogenic Tumor with Features of Calcifying Odontogenic Cyst in 3 Cats and a Dog

Abstract: This case series describes the clinical appearance, radiographic appearance and histopathologic features of 4 patients (3 cats and 1 dog) with unique cystic oral lesions that are consistent with a diagnosis of calcifying odontogenic cyst (COC). COC is a rare odontogenic lesion in humans that has not been previously reported in companion animals. Historically, COC in humans has been classified as a benign cystic neoplasm and as a non-neoplastic odontogenic cyst. Current classification favors the latter. The cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although reverse polarity was observed in ameloblastoma and ghost cell odontogenic lesions in humans were not observed in this case, other histological features were highly supportive of the diagnosis of GCOC. Even in COC case reports in dogs, distinctive reverse polarity of the cystic epithelium was not observed, but the overall histological findings were features of COC, as in this case (14). This may be due to interspecific differences between humans and dogs.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Although reverse polarity was observed in ameloblastoma and ghost cell odontogenic lesions in humans were not observed in this case, other histological features were highly supportive of the diagnosis of GCOC. Even in COC case reports in dogs, distinctive reverse polarity of the cystic epithelium was not observed, but the overall histological findings were features of COC, as in this case (14). This may be due to interspecific differences between humans and dogs.…”
Section: Discussioncontrasting
confidence: 51%
“…GOGCs are extremely rare epithelial odontogenic tumors in humans ( 8 , 12 , 13 ) that have not been previously reported in companion animals. Only one study reported the occurrence of COC, in one dog and three cats ( 14 ). Compared with COC and DGCT, GCOC exhibits high-grade malignant cellular features with necrosis and histological invasion ( 9 ).…”
Section: Introductionmentioning
confidence: 99%